Análise do impacto da adoção do IFRS 16 (CPC 06 (R2)) nas empresas de capital aberto do segmento novo mercado - Messias, Adriano Menezes (2021)
The IASB (International Acccounting Standards Board) developed a new standard for accounting for lease agreements, disclosing the IFRS 16 standard in early 2016. Following the rules of this standard, CPC 06 (R2) was developed in Brazil. The main change occurred in the leasing companies that previously classified the financial lease and operating lease, with the application of the standard as of January 2019, began to record the lease agreements in their balance sheets as off-balanced-sheet finance. According to this new accounting standard, this study aimed to verify the impact of the adoption of this standard on companies listed in [B] ³ in the new market. In order to verify this impact, calculations of the economic and financial indicators of the Standardized Financial Statements (SFSs) for the year 2019 were performed, making adjustments to these statements to verify how the indicators would be with and without the effect of applying IFRS 16. The values related to the rights of use assets, lease liabilities, financial expenses and depreciation of rights of use were adjusted. Lease payments made were subtracted from the income statement. The study suggests that with the adoption of the standard, there was a reduction in the immediataly liquidity index, quick ratio, current ratio, and total liquidity ratio. Regarding the equity structure indices, there was an increase in the debt index, fixed assets and non-current assets fixed assets and a reduction in the debt composition index. Reduction in the profitability indexes being asset turnover, net margin, profitability of the asset and profitability of the PL (not due to the reduction in profit but due to the increase in the capital asset and indebtedness structures). It was observed through the study that the cyclical consumption sector, which includes companies in the field of educational services, commerce and fabrics, clothing and footwear, was the most impacted with the adoption of the IFRS 16 standard and the public utility sector the least impacted